P‐72: Non‐Unified Elemental Image Array Generation Method for Moiré‐Reduced Integral Imaging System. Issue 1 (June 2015) - Xiong, Zhao‐Long; Chen, Jun; Deng, Huan; Wang, Qiong‐Hua
Abstract : In this paper, we propose a method based on selective pixel sampling algorithm to generate non‐unified integral imaging (II) elemental image array (EIA) with reduced moiré patterns at a smaller rendering cost and higher three‐dimensional (3D) resolution. In the proposed method, the redundant 3D information is captured for the non‐unified pixel arrangement of elemental images (EI) and the moire patterns are constrained by the constraint equations. The corresponding EIA's information is sampled from the obtained 3D information selectively. Appropriate experiments are carried out and the results show that the proposed method can increase the resolution of the reconstructed 3D images and reduce rendering cost markedly in the generation of ultra high‐definition (UHD) EIA.